EPISTEMIC JUSTICE AND CREATIVE AGENCY : global perspectives on literature and film. - Colvin, Sarah; Galasso, Stephanie ([S.l.] : ROUTLEDGE, 2022)
Foundational theories of epistemic justice, such as Miranda Fricker's,havecited literary narratives to support their case. But why have those narratives in particularprovided the resource that was needed? And is cultural production always supportive of epistemic justice? This essay collection, written by experts in literary,philosophical, and cultural studies working in conversation with each other across a range of global contexts, expands the emerging field of epistemic injustice studies. The essays analyze the complex relationship between narrative, aesthetics, and epistemic (in)justice, referencing texts, film, and other forms of cultural production.The authors present,without seeking to synthesize, perspectives on how justice and injustice are narratively and aesthetically produced. This volume by no means wants to say the last word on epistemic justice and creative agency. The intention isto openout aproductive new field of study, at a time when understanding the workings of injustice and possibilities for justice seems an ever more urgent project.
Keywords: Justice in literature; Justice, Administration of, in motion pictures; LITERARY CRITICISM / General